2012
DOI: 10.1021/la3015964
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pickering Emulsions Stabilized via Interaction between Nanoparticles Dispersed in Aqueous Phase and Polymer End Groups Dissolved in Oil Phase

Abstract: The influence of end groups of a polymer dissolved in an oil phase on the formation of a Pickering-type hydroxyapatite (HAp) nanoparticle-stabilized emulsion and on the morphology of HAp nanoparticle-coated microspheres prepared by evaporating solvent from the emulsion was investigated. Polystyrene (PS) molecules with varying end groups and molecular weights were used as model polymers. Although HAp nanoparticles alone could not function as a particulate emulsifier for stabilizing dichloromethane (oil) droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…A latter study further confirmed that the interactions between end groups of polymers and Hap nanoparticles at the oil–water interface were crucial in stabilizing Pickering emulsions as well as regulating the size of droplets and the morphology of products; the researchers chose polystyrene (PS) molecules with diverse end groups (like carboxyl groups, ester groups) and molecular weights to investigate their influence on the formation of Hap nanoparticle-stabilized droplets and MSs (Okada et al, 2012). Another work also utilized the interaction between the Hap nanoparticles and carbonyl/carboxylic acid groups, while the creative part was to add poly(ε-caprolactone) (PCL) which could dissolve in a wider range of organic solvents compared with another two polyesters, poly( L -lactic acid) (PLLA) and poly( L -lactide-co-glycolide) (PLGA); this means that non-halogenated solvents can be used (Fujii et al, 2012).…”
Section: Solid Particlesmentioning
confidence: 86%
“…A latter study further confirmed that the interactions between end groups of polymers and Hap nanoparticles at the oil–water interface were crucial in stabilizing Pickering emulsions as well as regulating the size of droplets and the morphology of products; the researchers chose polystyrene (PS) molecules with diverse end groups (like carboxyl groups, ester groups) and molecular weights to investigate their influence on the formation of Hap nanoparticle-stabilized droplets and MSs (Okada et al, 2012). Another work also utilized the interaction between the Hap nanoparticles and carbonyl/carboxylic acid groups, while the creative part was to add poly(ε-caprolactone) (PCL) which could dissolve in a wider range of organic solvents compared with another two polyesters, poly( L -lactic acid) (PLLA) and poly( L -lactide-co-glycolide) (PLGA); this means that non-halogenated solvents can be used (Fujii et al, 2012).…”
Section: Solid Particlesmentioning
confidence: 86%
“…Although no stable emulsion was obtained using oils without an ester group (e.g. dichloromethane), dichloromethane droplets could be stabilized by dissolving polymers having ester groups (or carboxyl terminal group) via the interaction between polymer and HAp nanoparticles at the oil/water interfaces [285,286]. It was also demonstrated that emulsification-demulsification cycles could be repeatedly achieved by pH adjustment, because the HAp-adsorbed emulsion droplets became unstable at lower pH (< 4) and the emulsion stability was recovered by raising pH.…”
Section: Particulate Emulsifier (Pickering Emulsion Stabilizer)mentioning
confidence: 99%
“…Polystyrene/nano‐SiO 2 composite microspheres with core/shell structure were synthesized in a Pickering emulsion route using nano‐SiO 2 particles as stabilizers . Okada et al supposed a method for the synthesis of Pickering emulsion stabilized via interaction between nanoparticles and polymer end groups. Gao et al constructed a Pickering emulsion stabilized by glucose oxidase and catalase‐containing silica particles.…”
Section: Introductionmentioning
confidence: 99%